The Influence of Audiovisual Learning Media on The Learning Outcomes of Underhand and Overhand Volleyball Serves At SMA Labschool Unesa 1 - Alfiana Putri, Dina Dwi; Sri Wahjuni, Endang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Physical education is a component of education that emphasizes physical activity, which is essential in the learning process. The primary goal of physical education is to enhance physical skills, motor abilities, emotional control, and a healthy lifestyle through well-planned programs of physical activities, sports, and health. Observations indicate that during PJOK lessons, especially on volleyball material, many students at SMA Labschool Unesa 1 show a lack of interest in participating in the lessons. The researcher uses audio-visual media, which is expected to help improve students' learning outcomes, particularly in the overhand and underhand serve in volleyball. The aim of this study is to determine the impact of audio-visual learning media on the learning outcomes of overhand and underhand serves. This research is a quantitative experiment using a randomized control group pretest-posttest design that includes an experimental group and a control group. The mean pretest score for the experimental group was 5.59 for the underhand serve and 5.62 for the overhand serve, while the posttest scores were 7.07 and 7.21, respectively. The standard deviation for the pretest underhand serve was 1.701 and for the overhand serve was 1.545; for the posttest, the underhand serve had a standard deviation of 1.602 and the overhand serve had 1.207. In the control group, the pretest scores were 5.33 for the underhand serve and 5.67 for the overhand serve; the posttest scores were 6.80 and 6.93, respectively. The standard deviation for the pretest was 1.755, and the posttest showed a result of 2.301. The research results indicate that the use of audio-visual media did not significantly affect students' learning outcomes, as the percentage results from both groups were low. Therefore, it is recommended that the use of audio-visual media in teaching volleyball basic techniques should more effectively integrate technology in the learning process. Additionally, teachers should provide more creative audio-visual lessons that are tailored to the course material and students needs.